An Exploration of Students’ Experiences in one DEIS second level school - Dwyer, Patricia (Trinity College Dublin. School of Education. Discipline of Education, 2022)
Existing qualitative studies on DEIS and the lived experiences of students in DEIS schools are limited, particularly at second level. There has not been much analysis of the ways in which the affective elements of education, particularly caring, influence the lives of students. This study was a single case study carried out in a second-level school designated as ‘disadvantaged’ and serving marginalized students in an area of economic, social and geographical disadvantage . It looked at the students’ experience in that DEIS school, using the conceptual lenses of student voice, power and empowerment, and the ethics of care. It has drawn on the work of Bourdieu, Freire, Shor and Noddings, among others, in relation to power and empowerment, social reproduction, the hidden curriculum and caring relations, key themes in this thesis. As a result, it adopts a social justice perspective, emphasising the benefits that the affective elements of schooling and authentic consultation with students can bring to individual students and school communities as a whole. This study explored students’ experience of school in terms of the place, the people and their experiences of both. It sought to explore the role of care in the context of schooling and examined how prioritizing the affective elements of education can bring about academic achievement and promote student wellbeing, particularly for students from challenging backgrounds. It explored how valuing and promoting student voice research can have a transformative impact on the student participants and on the school community as a whole. Focus group interviews were conducted with 42 students. This thesis presents the experiences of those students. The findings showed that the students identified three key themes as being critical to their engagement with school – their experience of care, positive relationships and a sense of belonging as being crucial to their engagement with school. By adopting a qualitative approach, this research challenges the heavy emphasis on accountability and measurement in most analysis of what is happening in DEIS schools.
Keywords: Student Voice; Care; Affective Education; Educational Inequity